KEPEMIMPINAN DAN CAPACITY BUILDING DALAM KONSTRUKSI PENINGKATAN MUTU MADRASAH ALIYAH SWASTA - Mukhlisuddin, Mukhlisuddin (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the role of leadership and capacity building strategies in the construction of improving the quality of madrasas in Madrasah Aliyah Private (MAS) Patra Mandiri Palembang. The approach used is descriptive qualitative with a case study design, which focuses on the leadership practices of madrasah heads, strengthening the capacity of human resources, and the implementation of the internal quality assurance system (SPMI). Data were obtained through in-depth interviews, participatory observations, and documentation studies, then analyzed with the interactive model Miles, Huberman, and Saldaña. The results of the study show that madrasah heads play the role of transformational leaders who combine Islamic values with modern management principles, building a reflective, collaborative, and quality-oriented culture. The capacity building strategy is implemented through continuous training, reflective supervision, and the formation of a professional learning community, which collectively strengthens the professionalism of teachers and the madrasah work climate. This finding confirms that the synergy between value-based leadership and capacity building is the main foundation in realizing the quality of religious, adaptive, and competitive madrasas. This research provides theoretical contributions to the development of Islamic education management as well as practical implications for policy makers in designing sustainable and contextual quality improvement models.